Young Children's Moral Judgments, Justifications, and Emotion Attributions in Peer Relationship Contexts. Issue 6 (6th June 2017) - Smetana, Judith G.; Ball, Courtney L.
Abstract : Children ( n =  160, 4‐ to 9‐year‐olds; M age  = 6.23 years, SD  = 1.46) judged, justified, attributed emotions, and rated intent for hypothetical physical harm, psychological harm, and resource distribution transgressions against close friends, acquaintances, disliked peers, or bullies. Transgressions against bullies were judged more acceptable than against friends and disliked peers and less deserving of punishment than against acquaintances and disliked peers. Transgressions against friends were judged least intended and resulting in more negative emotions for transgressors; actors transgressing against disliked peers, as compared to bullies or acquaintances, were happy victimizers. Across relationships, children viewed moral transgressions as wrong independent of rules and authority, based primarily on welfare and fairness justifications. Peer context colors but does not fundamentally change moral evaluations.